COMMUNITY PARTICIPATION: A NEW DEVELOPMENT IN EDUCATIONAL MANAGEMENT - Fika, Ibrahim Baba (Sokoto Educational Review, 2017)
Communities can play a variety of roles in the provision and management of education and learning processes. Community contribution to schools can go beyond the traditional financial contribution. It can however extend to a broader range of functions which include administrative (such as school maintenance), managerial (such as student and teacher discipline), financial (mobilizing of funds and resources), pedagogical (establishing a preschool), personnel (monitoring teacher attendance). The community is responsible for providing a harmonious working condition in school. The focus of the school, teaching methods, the focus of the curriculum as well as the school discipline are all ultimately desired from the community in which the school functions. If there is no harmonious and dynamic relationship between the community and school, education will be pallid, illusive and unable to make any positive impact on the learners’ behavior. It is therefore against this backdrop, that this paper examines community participation and effective school management.